Resistance to Formal Education of the Sedulur Sikep Kudus Community (The relevance of Islamic educational values to the educational values of Sedulur Sikep) - Khoeroni, Farid; Syukur, Fatah; Nurhadi, Agus (EDUKASIA, 2023)
This study aims to describe the rejection of formal education by the Sedulur Sikep community. This study uses James Scott's theory of resistance to describe the forms and characteristics of resistance to formal education in Sedulur Sikep Kudus. This study employed qualitative research methods with an ethnographic approach to obtain data on community resistance to formal education. The data collection was carried out using interviews, observation, and documentation. The results revealed that the forms of resistance carried out by the Sedulur Sikep Kudus community were closed forms of resistance. It can be interpreted as a conscious rejection of formal education through less systematic procedures. They consistently refuse to engage in formal education due to their commitment to upholding their ancestral traditions and teachings. Also, they harbor doubts about work-oriented formal education. Furthermore, the educational values taught by the Sedulur Sikep community align with Islamic educational values. This study limits its focus on the portrait of the Sedulur Sikep community's rejection of formal education and the relevance of Islamic educational values to the educational values of Sedulur Sikep Kudus. Consequently, further research is needed to complete this study.